Telomere shortening impairs alveolar regeneration. Issue 4 (11th March 2022) - Zhang, Xin; Shi, Mengting; Zhao, Xi; Bin, Ennan; Hu, Yucheng; Tang, Nan; Dai, Huaping; Wang, Chen
Abstract: Objectives: Short telomeres in alveolar type 2 (AT2) cells have been associated with many lung diseases. The study aimed to investigate the regeneration capacity of AT2 cells with short telomeres by knocking out Tert in mice (G4 Tert −/− ) from the whole to the cellular level. Materials and Methods: The lung injury model of mice was established by left pneumonectomy (PNX). The proliferation and differentiation of AT2 cells were observed by immunofluorescence staining in vivo and in vitro. The difference of the gene expression between control and G4 Tert −/− group during the regeneration of AT2 cells was compared by RNA sequencing. The expression of tubulin polymerization promoting protein 3 (TPPP3) was reduced by adeno‐associated virus delivery. Results: The alveolar regeneration in G4 Tert −/− mice was impaired after PNX‐induced lung injury. The regulation of cytoskeleton remodelling was defective in G4 Tert −/− AT2 cells. The expression of TPPP3 was gradually increased during AT2 cell differentiation. The expression level of TPPP3 was reduced in G4 Tert −/− AT2 cells. Reducing TPPP3 expression in AT2 cells limits the microtubule remodelling and differentiation of AT2 cells. Conclusion: Short telomeres in AT2 cells result in the reduced expression level of TPPP3, leading to impaired regeneration capacity of AT2 cells. Abstract : Short telomeres in alveolar type 2 (AT2) cells have been associated with many lung diseases. The study aimed to investigate the regeneration capacity of AT2 cells with short telomeres by knocking out Tert in mice (G4 Tert −/− ) from the whole to the cellular level. Our findings suggest that short telomeres in AT2 cells result in the reduced expression level of TPPP3, leading to impaired regeneration capacity of AT2 cells.